Bahasa Melayu dan Penyesuaian Budaya Siswa Antarabangsa di Universiti Swasta - Taib, Roslizawati; Ravana, Venosha (Development in Language Studies, 2023)
Bahasa Melayu Komunikasi courses have been implemented at the level of Malaysian higher education institutions and are now offered and required for all international students studying in Malaysia. However, the difficulties of applying what they’ve learned in everyday conversation while on campus have hindered and hampered their efforts to improve their command of the language. By using the teaching and learning model that is practiced in Bahasa Melayu Komunikasi 1 and 2 courses at higher education institutions, it cannot be denied that bilingualism’s delivery technique is necessary to facilitate the teaching and learning process. After completing the 14-week course, international students can read short passages, understand various vocabulary words, and write simple sentences in Malay. However, due to the learning environment and atmosphere in private universities that prioritise English as a communication and knowledge delivery medium, as well as the widespread use of the mother tongue among local students, especially in private universities, learning the Malay language is seen as still incapable of assisting international students in adapting to the Malaysian culture. According to several studies, international students need to be given plenty of space to communicate in Malay with their course mates to ensure that the language is not forgotten once the course is completed.